Development of science literacy-based animated video media for IPAS - Clara Lapebridinsi; Dea Mustika (Inovasi Kurikulum, 2025)
The lack of engaging learning media is one of the obstacles in the teaching and learning process, which affects students' low learning outcomes. This study aims to develop a science literacy-based animated video media for the Natural and Social Sciences (IPAS) subject in Grade IV at SDN 006 Pangkalan Indarung, Kuantan Singingi Regency. This research is a type of Research and Development (RnD) using the ADDIE development model. The research subjects included six validators consisting of two material experts, two language experts, and two design experts, as well as one teacher and six fourth-grade students. Data collection techniques involved validation sheets and response questionnaires, which were then analyzed using qualitative and quantitative methods. The validation results from all six validators indicated that the science literacy-based animated video media is highly valid in terms of content, language use, and visual design. In addition, responses from the teacher and students showed that the media is engaging, easy to understand, communicative, and relevant to the IPAS subject matter. Therefore, it can be concluded that this media is feasible to be used as a learning support tool that can enhance student engagement and understanding.   Abstrak Kurangnya media pembelajaran yang menarik menjadi salah satu kendala dalam proses belajar mengajar, yang berdampak pada rendahnya hasil belajar peserta didik. Penelitian ini bertujuan mengembangkan media video animasi berbasis literasi sains pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) kelas IV SDN 006 Pangkalan Indarung, Kabupaten Kuantan Singingi. Penelitian ini merupakan penelitian Research and Development (RnD) dengan menggunakan model pengembangan ADDIE. Subjek dalam penelitian ini meliputi enam validator yang terdiri atas dua ahli materi, dua ahli bahasa, dan dua ahli desain, serta satu guru dan enam peserta didik kelas IV. Teknik pengumpulan data menggunakan lembar validasi dan angket respon, yang kemudian dianalisis secara kualitatif dan kuantitatif. Hasil validasi dari keenam validator menunjukkan bahwa media video animasi berbasis literasi sains dinyatakan sangat valid dari segi isi materi, penggunaan bahasa, dan desain visual. Selain itu, respon guru dan peserta didik menunjukkan bahwa media ini menarik, mudah dipahami, komunikatif, dan relevan dengan materi IPAS. Oleh karena itu, dapat disimpulkan bahwa media ini dinilai layak digunakan sebagai sarana pendukung pembelajaran yang mampu meningkatkan keterlibatan dan pemahaman peserta didik. Kata Kunci: media video animasi; literasi sains; IPAS